The Effect of Deposition Parameters on the Growth Rate of Microcrystalline Diamond Powders Synthesized by HFCVD Method - Tao Zhang (Coatings, 2017)
Conventional diamond powders (<10 μm) are generally produced from crushing large-sized diamonds synthesized by high-pressure and high-temperature (HPHT) technique, whereas they have many morphological imperfections. In the present work, these powders are served as diamond seeds and regrown by hot filament chemical vapor deposition (HFCVD). Deposition parameters—such as the carbon concentration, substrate temperature, and bias current—which play a determined role in the homoepitaxial growth rate of micron diamonds, are investigated in their respective usual ranges. As shown in the experimental results, under the preconditions of maintaining the good morphology of crystals and inhibiting polycrystal growth, the growth rate of isolated diamond crystals can be controlled at 0.9 μm/h. Besides, the final improved powders have a wide range of particle sizes, which could fail to meet the requirements for commercial powders without the post-process of sieving.